How to conduct a clinical audit and quality improvement project. Issue 6 (July 2017) - Limb, Christopher; Fowler, Alex; Gundogan, Buket; Koshy, Kiron; Agha, Riaz
Abstract : Audits and quality improvement projects are vital aspects of clinical governance and continual service improvement in medicine. In this article we describe the process of clinical audit and quality improvement project. Guidance is also provided on how to design an effective audit and bypass barriers encountered during the process.